Earnings Management in Banking Industry And Its Impact on The Firm Value - Abbas, Ahmad (UNIVERSITAS NEGERI SURABAYA, 2018)
This research investigates earnings management through discretionary accruals in pre and post period of convergence of IFRS and analyses its impact on the firm value in Indonesian banking industry. The sample of this research was 23 banks listed in Indonesia Stock Exchange over period of 2007-2014.Â The method of this research is quantitative. The data are analyzed using the non-paramateric Wilcoxon Signed Ranks and the multiple regression. The result of this research found that accrual earnings management has no the mean difference in pre and post period of convergence of IFRS. Based on the effect of earnings management on banking firm value, it was found that banking earnings management has an impact on the increase of the firm value. This research further identifies the patterns in accrual earnings management including income-increasing and income-decreasing. Both patterns induced managers to increase the firm value. This research also found that that income-decreasing pattern has a stronger impact on the increase of the firm value than income-increasing pattern.